Primary Outcomes of Patients with Chronic Angle-Closure Glaucoma Treated with Combined Phacoemulsification, Viscogoniosynechialysis, and Endocyclophotocoagulation - Juan Carlos Izquierdo Villavicencio; Natalia Agudelo Arbelaez; Bárbara Rubio Lastra; Imelda Ramirez; Fabiola Quezada; Maria Corina Ponte; Laura Cañola; Josefina Mejias Smith (Journal of Ophthalmology)
Purpose/Objective. To evaluate the effectiveness of combined phacoemulsification, viscogoniosynechialysis (VGSL), and endocyclophotocoagulation (ECP) in patients with moderate chronic angle-closure glaucoma (CACG) with peripheral anterior synechia (PAS) ≥90 not controlled with glaucoma medications and previous iridotomy yag laser. Materials and Methods. We retrospectively reviewed records from patients with cataract and uncontrolled chronic angle-closure glaucoma despite maximal tolerated medical therapy and iridotomy yag laser who received combined treatment with phacoemulsification with posterior capsular lens implantation, VGSL, and ECP 360°. We evaluated intraocular pressure (IOP), glaucoma medications, and best corrected visual acuity (BCVA) preoperatively and during follow-up.Results. A total of 29 eyes from 22 patients received surgical intervention. Mean follow-up was 6 months. Mean preoperative IOP was 18.2 mmHg, and postoperatively, IOP was 13.5, 12.2, and 12.8 mmHg at 1, 3, and 6 months, respectively. Complete success was 37.9%, and relative success was 72.4%. Mean BCVA was 0.4 logMAR preoperative and 0.3 logMAR 6 months after surgery. Glaucoma medication fell significantly from 2.34 ± 1.66 preoperatively to 1.31 ± 2.6 postoperatively p<0.001. Overall, 44.8% of the patients did not require glaucoma medications at 6 months. There were no visual significant complications. Conclusion. Combined treatment with phacoemulsification with posterior capsular lens implantation, VGSL, and ECP is effective and safe in reducing IOP and number of glaucoma medications with stable BCVA at 6 months.